Bite force measurements for objective evaluations of orthodontic tooth movement-induced pain in rats. (May 2019) - Long, Hu; Shan, Di; Huang, Renhuan; Liu, He; Zhou, Yang; Gao, Muyun; Jian, Fan; Wang, Yan; Lai, Wenli
Highlights: Bite force is a viable and reliable objective index for the evaluation of orthodontic pain. Periodontal administrations of NGF could completely mimic orthodontic pain. Periodontal administrations of NGF neutralizing antibody could completely abolish orthodontic pain. Periodontal injections of CFA could reduce bite force in rats. Abstract: Objective: To examine the reliability of bite force for evaluating orthodontic tooth movement-induced pain in rats. Design: Orthodontic tooth movement-induced pain was induced by mounting springs (40 g) between incisors and ipsilateral molars in male Sprague-Dawley rats. Five group sets of animals were used: for the first group set, 20 rats were randomly divided into a force group (n = 10) and a sham group (n = 10); for the second group set, 20 rats were divided into a 20-g group and a 80-g group; for the third group set, 20 rats were randomly divided into either a CFA group (complete freund's adjuvant) (n = 10) receiving periodontal injections of CFA at baseline or a control group (n = 10) receiving periodontal injections of saline at baseline; for the forth group set, 24 rats were randomly divided into the following four groups: force + saline, control + saline, force + antiNGF and control + NGF (NGF: nerve growth factor). Rats in the fifth group set were used for immunostaining against CGRP. Bite force and bite frequency were measured at baseline (day 0) and following interventions (day 1, day 3, day 5, day 7 and day 14). Two-way ANOVA with repeated measures was used for statistical analysis and a p value less than 0.05 was considered statistical significance. Results: Our results revealed that bite force was significantly smaller in the force group than in the sham group at all time points (p < .001). As compared to the control group, periodontal injections of CFA significantly decreased bite force on the 3rd day (p < .01). Moreover, bite force was significantly higher in the force + antiNGF group than in the force + saline group (p = .01 < .05) while significantly smaller in the control + NGF group than in the control + saline group (p < .05). Bite force was similar between the force + antiNGF group and the control + saline group (p = .71 > .05) and between the control + NGF group and the force + saline group (p = .58 > .05). Similar results were found for bite frequency.